Abdurrahman Wahid (Gus Dur): Sufisme Transformatif - Edi Nurhidin; Ngainun Naim; Muhammad Fahim Dinana (Religia, 2022)
This paper observes the idea of Abdurrahman Wahid's Sufism. It is important to study Sufism in the strengthening of dual morality in Indonesian Muslims. It is to complement the development of contemporary Sufism discourse in the archipelago as well. The research method of this paper was a literature review. The data used in this paper were the works of Abdurrahman Wahid in the form of a collection of articles, bookkeeping of 'preface', and 'preface' which were scattered in several other people's books as well as other relevant writing sources. The data that had been collected were then analyzed using a qualitative content analysis method according to the topic of the writing. The results of this research found that Abdurrahman Wahid's idea of Sufism contributed significantly to the realization of the basic values and teachings of Islam in the life of religion, society, nation, and state. It indicates that Abdurrahman Wahid has transformed the meaning and actualized Sufism from and for Sufism. Love and compassion play a central role at the core of Sufism which is actively manifested in social life to fight for human values and principles.